Trajectories towards the neolithisation of NW Turkey - Thissen, Laurens (Documenta Praehistorica, 1999)
This paper consider diverse trajectories concerning the origin of some early farming villages in Northwestern Turkey during the beginnings of food producing economies in this part of the country. The roots for the process are sought in the Konya area on the Central Anatolian Plateau. The ceramic assemblages of the first farming sites of the northwest are believed to be a reproduction of the pottery tradition best known from Çatal Höyük East, both technologically, morphologically and as regards manipulation and use. In individual sites , the present state of research allows contemplation both of migration and mesolithic adaptation to explain for the transition to neolithic subsistence modes.
Keywords: archaeology; arheologija; arheološke najdbe; ceramic; keramika